Mutualism Based on Stress: Selective Synthesis and Phosphorylation of a Stress Protein by an Intracellular Symbiont - Morioka, Mizue; Ishikawa, Hajime (Journal of biochemistry (Tokyo), 1992)
The effects of a temperature shift-up and various metabolic inhibitors on the protein synthesis of an endosymbiont isolated from the pea aphid were studied. The syntheses of at least three major polypeptides were stimulated transiently immediately after a temperature shift-up, and treatment with ethanol and heavy metals (Cd2+ and As2+). One of these proteins, the 63kDa heat-shock protein (63-kDa HSP), was immunoprecipitated with antiserum raised against symbionin, which is selectively synthesized by the endosymbiont harbored by the aphid bacteriocytes. The 63 kDa heat-shock protein has a molecular mass of 800 kDa and is more acidic than symbionin. It was also shown that symbionin is subject to phosphorylation in vivo and in vitro after a temperature shift-up. It was thought likely that forms of environmental stress such as heat shock and metabolic inhibitors stimulate the synthesis of a phosphorylated form of symbionin. It was also suggested that the in vitro phosphorylation of symbionin is due to its own catalytic activity. Since symbionin is a homolog of the Escherichia coli groEL protein, a stress protein, it is likely that the endosymbiont suffers stress when harbored by the bacteriocytes and responds in a similar manner to environmental stress when outside these cells.